Natural in situ relationships suggest coral reef calcium carbonate production will decline with ocean acidification. (11th February 2015) - Shaw, Emily C.; Phinn, Stuart R.; Tilbrook, Bronte; Steven, Andy
Abstract There are few in situ studies showing how net community calcification (Gnet) of coral reefs is related to carbonate chemistry, and the studies to date have demonstrated different predicted rates of change. In this study, we measured net community production (Pnet), Gnet, and carbonate chemistry of a reef flat at One Tree Island, Great Barrier Reef. Diurnal pCO2 variability of 289–724 μatm was driven primarily by photosynthesis and respiration. The reef flat was found to be net autotrophic, with daily production of ∼ 35 mmol C m−2 d−1 and net calcification of ∼ 33 mmol C m−2 d−1. Gnet was strongly related to Pnet, which drove a hysteresis pattern in the relationship between Gnet and aragonite saturation state (Ωar). Although Pnet was the main driver of Gnet, Ωar was still an important factor, where 95% of the variance in Gnet could be described by Pnet and Ωar. Based on the observed in situ relationship, Gnet would be expected to reach zero when Ωar is ∼ 2.5. It is unknown what proportion of a decline in Gnet would be through reduced calcification and what would occur through increased dissolution, but the results here support predictions that overall calcium carbonate production will decline in coral reefs as a result of ocean acidification.